The effect of manganese exposure on erythropoietic and reproductive system parameters - Servet Birgin Iritas; Lutfiye Tutkun; Meside Gunduzoz; Serdar Deniz; Vugar Ali Turksoy (Medicine Science, 2018)
The aim of this study is determining the effect of manganese (Mn) exposure on erythropoietic and reproductive system. A study group consisting of 51 non-smoking welders older than 18 years old with Mn exposure, who visited Ankara Occupational and Environmental Diseases Hospital, and a control group consisting of 79 healthy office employees without Mn exposure, were chosen as study group. Blood Mn level, total testosterone (TT), freetestosterone (FT), alanine aminotransferase (ALT), aspartate aminotransferase(AST), thyroid stimulant hormone (TSH), triiodothyronine (T3), thyroxine (T4), uric acid, creatinine, complete blood count (CBC), prolactin, follicle stimulating hormone (FSH), luteinizing hormone (LH) levels were analysed along with the demographic data of the patient. The study and control groups consisting of a total of 130 persons were all male, 39.2% (n=51) of which represented the study group with manganese exposure and 60.8% (n=79) of which represented the healthy control group. A significant difference was identified statistically between Mn (t= 4,501, p= 0,000), FT (t= -6.959, p=0.000), TT (t= -2.835, p=0.005) values of those with and without manganese exposure. AST and ALT levels were not found significant although they were higher in the exposed group. When the values are examined according to uric acid, creatinine, TSH, T3, T4and complete blood count, it was observed that the values of exposure group and control group were almost identical. Although FHS, LH and PRL values were high in the study group, the differences were not found significant. Consequently, although Mn is a trace element, it was concluded that, in high levels,it might reduce the testosterone synthesis with direct toxic effect on the testicle in the long-term exposures leading. [Med-Science 2018; 7(4.000): 817-20]